Moral Permissibility of Action Plans - Lindner, Felix; Mattmüller, Robert; Nebel, Bernhard (Proceedings of the AAAI Conference on Artificial Intelligence, 2019)
Research in classical planning so far was mainly concerned with generating a satisficing or an optimal plan. However, if such systems are used to make decisions that are relevant to humans, one should also consider the ethical consequences generated plans can have. We address this challenge by analyzing in how far it is possible to generalize existing approaches of machine ethics to automatic planning systems. Traditionally, ethical principles are formulated in an actionbased manner, allowing to judge the execution of one action. We show how such a judgment can be generalized to plans. Further, we study the computational complexity of making ethical judgment about plans.